Water Transport: a systematic Review Analysis of Patenty and Literature RSL) on the impacts of the Internet of Things in the context of smart cities post ODS 11 - Barreto, Wagner Alves (2023)
The main technological solutions in the field of water transport are aligned to meet the demands of Smart Cities through the integration of mobility services and the Internet of Things. A literature analysis was performed on the Scopus database, using the terms "navigation", "waterway", "waterway" and "IoT", excluding the terms "air" and "aviation", in the period from 1985 to 2022, resulting in 567 documents. Patents obtained by Orbit Intelligence with IPC codes similar to the terms in the literature were also analyzed, such as G21C 11/04, F21W 111/04, G16Y-010/75, G16Y-040/60 and B63B 23/46, limited to the priority first year patents from 2000 to 2019, thus totaling 1,076 patents. The progress of IoTs in this mode of transport was identified, the predominance of China and Electronic Samsung, and the peak that these technologies reached after SDG 11, which refer to resilient cities and communities.